A combined actinometry approach for medium pressure N2–O2 plasmas. (8th January 2021) - Caplinger, James E; Perram, Glen P; Adams, Steven F
Abstract: An argon actinometry approach which uses the 777 nm and 844 nm atomic oxygen lines along with the common N2 / N 2 + line ratio method is used to experimentally investigate the excitation mechanisms of the O(3p 5 P) state in medium pressure (0.75 Torr) N2 –O2 plasmas. The method provides strong evidence that metastable excitation from the O(3s 5 S ◦ ) state is an important excitation mechanism for O(3p 5 P) state for these conditions. The strong dependence of this additional mechanism on electron density along with the use of the N2 / N 2 + line ratio method allow for the simultaneous determination of effective electron temperature, dissociation fraction, metastable O(3s 5 S ◦ ) density and electron density. Predicted electron temperatures, electron densities and dissociation fractions are consistent with those found for similar discharges in prior studies. Additionally, we investigate the efficacy of using the observed 616 nm atomic oxygen line from the O(4d 5 D ◦ ) state for actinometry, which could open the door to a novel and comprehensive actinometry technique.